Problem Based Learning Learning Model improve Critical Thinking Ability - Yulianti, Deviana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The demands of the 2013 curriculum ideally are that learning is able to develop 4C skills, one of which is critical thinking and problem-solving skills (Critical-Thinking and Problem-Solving Skills), namely being able to think critically, laterally, and systematically, especially in the context of problem solving. In fact, students' critical thinking skills have not been maximally developed, especially in elementary schools. The learning process in elementary schools currently requires problem-based learning that requires students to actively carry out investigations in solving problems and the teacher acting as a facilitator or learning guide will be able to shape the ability of students to think critically. The purpose of this research is to describe the concept of Problem Based Learning (PBL), the concept of critical thinking ability, and the relationship between Problem Based Learning (PBL) and critical thinking ability. The results of the Problem Based Learning (PBL) model improve critical thinking ability.